If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1yx = 5 Solving 6x + -1xy = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Reorder the terms: -5 + 6x + -1xy = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + 6x + -1xy = 0 The solution to this equation could not be determined.
| ln(5-3)=ln(5)-ln(3) | | c(x)=7x+569 | | 52=c-46 | | x(x+8)-(25x+3x)=0 | | (-7+9i)+(2-10i)= | | -3x-2y+z=11 | | 6x-77+7x+11=4x-60+3x | | 12x-45=26-3x-4 | | 5x^2+2c+7=0 | | r-46=15 | | 6x-77-7x+11=4x-60-3x | | 30=3v | | x=3-1y | | 7=56j | | 750-50x=-185 | | 2ln(7x)=5 | | y-4.1=5.4 | | a^2+12a-21=0 | | X+(11)=13 | | 3b-5=-44 | | 42x^2-18x= | | ln(5+3)=ln(5)+ln(3) | | E-14=0 | | 21=b-6 | | c+7=9 | | y=20(.682) | | y=20(1.025) | | a+4=35 | | 8(1-3x)=7(3x-1) | | x^2-mx-(m^2-5)=0 | | 4y-9=11y-23 | | (5-2i)-(3+3i)= |